Effect of surfactant application practices on the vertical transport potential of hydrophobic pesticides in agrosystems - Dollinger, Jeanne; Schacht, Veronika J; Gaus, Caroline; Grant, Sharon (Chemosphere, 2018)
Surfactants have the potential to modify the environmental behavior of hydrophobic pesticides leading to an enhanced or reduced mobility risk. This risk is often overlooked in registration procedures due to a lack of suitable methodologies to quantify the transport potential of pesticides with surfactants. In this study we present a novel methodology designed to study the surfactant facilitated transport of pesticides under controlled equilibrium and dynamic hydrologic conditions. Using this methodology, we investigated the risk of chlorpyrifos enhanced mobility for two common surfactant application practices in agrosystems: pesticide spraying and irrigation with waste water. With the dynamic experiments we showed that a single irrigation event with artificial reclaimed water containing the nonionic surfactant Triton X100 at a concentration of 15 mg/L reduced the leaching of chlorpyrifos by 20% while the presence of the same surfactant in the chlopyrifos spraying formulation reduced the leaching amount by 60%. However, in the first case 90% of the chlropyrifos fraction remaining in soil was retained in the upper 3 cm while in the second cas, 72% was transported to the bottom layers. The presence of Triton X100 in irrigation water or spraying formulation retards the leaching of chlorpyrifos but enhances its downward transport.
Keywords: Hydrophobic pesticides; Pesticides; látky znečišťující půdu; povrchově aktivní látky; Surfactants; Mobility; pesticidy; Sorption; Soil-water partition coefficient; Risk assessment; Soil Pollutants; Surface-Active Agents